PENGARUH MINAT BACA DAN MOTIVASI BERPRESTASI TERHADAP KEMAMPUAN MEMAHAMI BACAAN DALAM BAHASA INGGRIS - Soleha Soleha; Syahfitri Purnama (INFERENCE: Journal of English Language Teaching, 2018)
This research is a survey and aims to find out and analyze empirically the effects of reading interest and need achievement towards student's reading comprehension on English text. The observed population of this research is students from a state senior high schools in North Jakarta. The sample was simple random sampling, which means that the researcher mixed the subjects in the population so that they will be considered the same. The results of this research are: 1) There are significant effects of reading interest and need achievement altogether towards reading comprehension on English text. It is proved by Sig.= 0.000 < 0.05 and Fobserved = 63.825; 2) There is a significant effect of reading interest towards student's reading comprehension on English text. It is proved by Sig.= 0.000 < 0.05 and tobserved = 6.476; 3) There is a significant effect of need achievement towards student's reading comprehension on English text. It is proved by Sig.= 0.001 < 0.05 and tobserved = 3.469.